Converting Biochar Into Biochar‐Based Urea Promotes Environmental and Economic Sustainability in Rice‐Wheat Rotation System - Xueliu Gong; Wei Shi; Jiarong Wu; Jingsong Qin; Wang Huang; Yanfang Feng; Haijun Sun; Jufeng Zheng; Kun Cheng; Stephen Joseph; Junhui Chen; Rongjun Bian; et al. (GCB Bioenergy, 2025)
ABSTRACT Biochar amendments in rice‐wheat systems are sustainable for reducing GHGs (greenhouse gases) and improving soil health but the widespread adoption of biochar faces economic challenges. To address limitation, a novel biochar‐based urea was formulated for environmental and cost advantages. A pot experiment within a rice‐wheat rotation was conducted to evaluate comparative effects of biochar‐based urea (CKBU), biochar + urea (BCU), and biochar‐based urea + biochar (BCBU) over conventional mineral fertilizer (CKU) on soil ammonia (NH3) volatilization, GHG emissions, soil structure, and crop productivity. Furthermore, fertilizer N fate was tracked using the 15N isotope during wheat season. The results indicated that compared to CKU, CKBU, BCU, and BCBU treatments significantly mitigated NH3 volatilization by 22%–31% during the rice season, and a 19% reduction was observed under the BCBU treatment during the wheat season due to the response of N‐cycling microorganisms. Regarding GHG emissions, the CKBU, BCU, and BCBU treatments significantly decreased the global warming potential (GWP) value by 49%–55% during the rice season and by 26%–45% during the wheat season, compared to CKU. Additionally, CKBU enhanced 15N use efficiency by 29% during wheat season, without affecting the rice season. The economic performance indicated that applying BU alone offered a net economic benefit, whereas biochar amendment led to a net economic loss. However, biochar amendment improved SOC and aggregation structure, with a significant increase in macroaggregate distribution over 50% compared to CKU and CKBU. Therefore, BU with small portions of biochar can be as effective in reducing NH3 emissions and mitigating GHG emissions as the use of a large quantity of biochar. Additionally, the BCBU did not show additional synergistic benefits regarding emission reduction or yield enhancement. Therefore, shifting biochar to BU could be a cost‐effective approach to achieving sustainable productivity in rice‐wheat crop rotation systems.